(untitled) (World Bulletin of Public Health, 2025)
This study investigated the clinical and laboratory characteristics of immune system disorders and endothelial dysfunction in patients with chronic glomerulonephritis (CG). Also, the level of antibodies against the A2 phospholipase receptor (PLA2R) of renal podocytes - anti-PLA2R - was determined and its diagnostic significance was assessed. According to the results of the study, the level of anti-PLA2R was significantly increased in primary membranous nephropathy, which indicated that this marker is a diagnostic criterion with high sensitivity and specificity. In secondary membranous and IgA nephropathies, the level of anti-PLA2R remained unchanged.